Ultrafast spectroscopy of La2-xSrxCuO4 single crystals - Bianchi, G; Chen, C; Ryan, J (2003)
We present measurements of the ultrafast optical response of La2-xSrx CuO4 single crystals at two different doping levels (x=0.15, 0.07) as a function of temperature. Owing to the 40-fs time resolution of our experiment, we are also to measure both the build-up and the decay of the ultrafast signal. We show for the first time that the temperature dependence of the transient reflectance amplitude tracks the thermal depletion of the superfluid density. At low temperature we identify a new regime characterized by an extremely long, temperature-dependent rise-time (3 ps). The doping dependence of the relaxation rate suggests that this is sensitive to the scattering of quasiparticles by low-energy spin excitations.